Acute alcohol intake alters resting state functional connectivity of nucleus accumbens with pain-related corticolimbic structures. (1st February 2020) - Boissoneault, Jeff; Stennett, Bethany; Robinson, Michael E.
Highlights: Growing evidence suggests common neural underpinnings of pain and alcohol effects. Alcohol intake reduced functional connectivity between mesocorticolimbic regions. Collectively, these regions underlie reward, motivated behavior, and pain response. Abstract: Background: The nucleus accumbens (NAc) is a ventral striatal structure underlying reward, reinforcement, and motivation, with extensive anatomic and functional connections to a wide range of affective processing structures (medial prefrontal cortex (mPFC), amygdala, and insula). Characterizing how acute alcohol intake affects resting state functional connectivity (rsFC) between the nucleus accumbens (NAc) and these regions will improve mechanistic understanding of alcohol's neurobehavioral effects, including the neural overlap between acute alcohol effects and pain processing. Methods: Fifteen healthy social drinkers (10 women; age: 25–45 years) were included in the study. Participants completed one session in which they consumed an alcohol dose targeting a breath alcohol concentration of 0.08 g/dL, and in a second a placebo beverage. Nine-minute resting state fMRI scans were acquired 30−35 min after beverage administration during each session. rsFC between NAc and a priori corticolimbic regions of interest (mPFC, amgydala, and insula), were compared between beverage conditions. We also conducted an exploratory whole-brain seed-to-voxel analysis of NAc FC. Results: Alcohol intake reduced rsFC between NAc and mPFC, as well as NAc and amygdala. Alcohol also reduced rsFC between NAc and a 97-voxel cluster including bilateral paracingulate cortex and anterior cingulate cortex. Conclusions: Findings suggest that acute alcohol intake reduces rsFC between NAc and several structures, including mPFC, amygdala, and rostral ACC in healthy social drinkers. These structures underlie reward, motivated behavior, and emotion regulation, and may provide mechanistic insight to how alcohol affects related processes, including pain.